Preparation method of heat-conducting adhesive, heat-conducting adhesive, battery and electric device
The use of a dispersion disk and controlled stirring speeds, along with dehydration and additive enhancements, addresses the dispersion issues in thermally conductive adhesives, resulting in improved adhesion and stability, thereby enhancing the bonding performance and reliability of the adhesive.
Patent Information
- Application Number
- CN202310753279.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing thermally conductive adhesives face issues with uneven dispersion of inorganic fillers leading to agglomeration, which reduces adhesion and shear resistance due to stress concentration and inhibited interaction between adhesive components, resulting in decreased bonding performance.
A preparation method using a dispersion disk with a stirring speed ranging from 300rpm to 2000rpm to achieve uniform dispersion of inorganic fillers, combined with dehydration and inert atmosphere to enhance dispersibility and stability, and the inclusion of additives like tackifiers, antioxidants, and anti-ultraviolet absorbers to improve adhesion and storage stability.
The method results in a uniformly dispersed thermally conductive adhesive with improved adhesion, shear resistance, and storage stability, effectively addressing the issues of agglomeration and premature curing, enhancing the bonding performance and reliability of the adhesive.
Smart Images

Figure CN119193079A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal conductive adhesives, and in particular to a preparation method of thermal conductive adhesives, thermal conductive adhesives, batteries and electrical devices. Background Art
[0002] Thermally conductive adhesives include polyurethane or epoxy resins, etc. Thermally conductive adhesives have a heat-conducting function. For example, a heating device generates heat, which can be conducted and dissipated through the thermally conductive adhesive.
[0003] One application scenario is to use thermally conductive adhesive to dissipate heat in power batteries. Power batteries generate a lot of heat during the charging and discharging process, and the heat needs to be dissipated as quickly as possible. In low-temperature environments, heating is required to transfer heat to the inside of the battery. In order to reduce the air gap and improve thermal conductivity, a thermally conductive medium needs to be filled between the battery heat dissipation surface and the cooling system. Thermally conductive adhesive is a commonly used thermally conductive medium. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for preparing a thermally conductive adhesive, aiming to improve the bonding performance of the thermally conductive adhesive.
[0005] To achieve the above object, the present invention provides a method for preparing a thermally conductive adhesive, comprising:
[0006] Preparing a formulation component of a thermally conductive adhesive, wherein the formulation component of the thermally conductive adhesive includes a prepolymer, a cross-linking agent, a catalyst, and an inorganic filler;
[0007] The formula components are heated and stirred to obtain a thermal conductive adhesive, wherein the stirring method includes stirring with a dispersion disk, and the stirring speed ranges from 300 rpm to 2000 rpm.
[0008] Considering that in the preparation process of thermal conductive adhesive, there will be uneven dispersion of inorganic fillers and agglomeration of inorganic fillers, which will cause the prepared thermal conductive adhesive to have particles, thereby causing a decrease in adhesion. Specifically, unevenly dispersed inorganic fillers will cause agglomerates and gels, causing stress concentration and damage during the tensile shear process, reducing the shear resistance of the bond. Agglomerates and gels inhibit the interaction between the adhesive components in the thermal conductive adhesive and the inorganic fillers, thereby reducing the cohesion (adhesion) of the adhesive, causing a decrease in adhesion and shear force.
[0009] For example, inorganic fillers include but are not limited to inorganic pigments or inorganic flame retardants. These substances have soft agglomerate and hard agglomerate particles. It can be understood that soft agglomerate refers to the agglomeration formed by short-range surface forces such as electrostatic attraction, van der Waals force or capillary force between primary particles, and hard agglomerate refers to the existence of chemical bonds in addition to the van der Waals force and Coulomb force between particles in the hard agglomerate.
[0010] For example, when the thermal conductive adhesive formula is dehydrated or polymerized at a certain temperature, it cannot provide corresponding self-shearing force. The inorganic fillers in the thermal conductive adhesive formula (such as inorganic minerals, including but not limited to calcium carbonate, talc, zinc borate, magnesium hydroxide, aluminum hydroxide, magnesium oxide, aluminum oxide, boron nitride, etc.) are particles with soft agglomerates and hard agglomerates and cannot be effectively dispersed in the thermal conductive adhesive formula.
[0011] In order to solve the above problems, the present application adopts a stirring method of a dispersion disk, and at a certain rotation speed (300rpm to 2000rpm), mechanical shearing is performed by relying on the high-speed flow field of the dispersion disk to obtain a uniform and delicate thermal conductive adhesive.
[0012] It can be understood that the dispersion disc is an accessory for the high-speed disperser, which is connected to the main shaft of the high-speed disperser. When the main shaft of the disperser runs at high speed, the dispersion disc rotates and a turbulent area is formed at the edge.
[0013] The dispersing disc is provided with dispersing teeth. It is understood that the toothed dispersing disc is a type of vortex agitator. The outer edge of the dispersing disc is serrated. The shearing performance is very high under high-speed rotation, and the breaking and crushing effect is strong. It is suitable for dispersing and mixing of two phases with large differences in physical properties, such as the dispersion process of coatings. The applicable speed of the toothed dispersing disc is very high, much higher than that of the paddle agitator. During the high-speed rotation process, the dispersing teeth of the dispersing disc shear, crush and disperse the material multiple times, thereby breaking up and mixing the agglomerated particles in the slurry to achieve uniform mixing of the slurry.
[0014] That is, the present application adopts dispersion disk stirring in the preparation process, and the stirring speed range is 300rpm to 2000rpm. The disk surface of the dispersion disk is provided with dispersion teeth. When running at high speed, the dispersion disk is in a rotating state. At the same time, a turbulent zone will be formed at the edge of the dispersion teeth to accelerate the mixing and mechanical shearing of the materials. The speed is in the range of 300rpm to 2000rpm, which can improve the phenomenon of particle generation. If a stirring paddle, stirring rod, etc. are used, the speed is in the range of 300rpm to 2000rpm, and particles will still be generated. The main reason is that even if the speed is faster, based on the fact that the stirring paddle and stirring rod have no dispersion teeth, the mechanical shearing effect of the material is not as good as that of using a dispersion disk, which still leads to the generation of particles.
[0015] It is also understandable that the particles present in the thermally conductive adhesive will cause the adhesive force of the thermally conductive adhesive to decrease. Specifically, unevenly dispersed inorganic fillers will cause agglomerates and gels, resulting in stress concentration and damage during the tensile shear process, reducing the shear resistance of the bond. Agglomerates and gels inhibit the interaction between the adhesive components in the thermally conductive adhesive and the inorganic fillers, thereby reducing the cohesion (adhesion) of the adhesive, causing a decrease in adhesion and shear force. The present application improves the adhesion of the thermally conductive adhesive by using a dispersion disk for stirring during the preparation process, at a certain speed, to increase the dispersibility of the inorganic filler.
[0016] In the present application, the types of prepolymer and cross-linking agent are not specifically limited. For example, when the thermal conductive adhesive is of polyurethane type, the prepolymer includes a hydroxyl-containing compound, and the cross-linking agent includes an isocyanate-containing compound.
[0017] In addition, the present application adopts a single-component preparation process during the preparation process. Compared with the need to prepare component A and component B separately and then mix components A and B to prepare the thermal conductive adhesive, the preparation method of the present application is simpler.
[0018] Optionally, during the heating and stirring of the formula components, the stirring speed ranges from 600 rpm to 1000 rpm.
[0019] It is understandable that increasing the rotation speed can improve the phenomenon of particle generation. Considering the equipment cost issue, for example, the higher the rotation speed, the higher the requirements for the equipment, and the higher the cost and maintenance requirements of the equipment. Therefore, in the process of heating and stirring the formula components, the stirring speed can range from 600rpm to 1000rpm.
[0020] Optionally, the step of heating and stirring the formula components to obtain the thermal conductive adhesive includes:
[0021] The prepolymer and the inorganic filler are mixed and stirred and dehydrated by a dispersion disk to obtain a dehydrated mixture;
[0022] Mixing the cross-linking agent with the dehydrated mixture, heating and stirring under an inert atmosphere to obtain a mixed intermediate product;
[0023] The catalyst is added into the mixed intermediate product, and the mixture is heated and stirred to obtain a thermal conductive adhesive.
[0024] In the process of heating and stirring the formulation components, the prepolymer and the inorganic filler are mixed and stirred and dehydrated by a dispersion disk to obtain a dehydrated mixture; that is, the prepolymer and the inorganic filler are mixed by a dispersion disk at a stirring speed of 300 rpm to 2000 rpm, which can effectively disperse the inorganic filler.
[0025] At the same time, considering that the raw material contains water, which will cure the thermally conductive adhesive prematurely, that is, during the storage of the thermally conductive adhesive, the water in the thermally conductive adhesive will react with the isocyanate group (NCO) in the thermally conductive adhesive (for example, taking the cross-linking agent as an isocyanate compound as an example), thereby curing the thermally conductive adhesive and reducing the storage stability of the thermally conductive adhesive. In addition, the cured thermally conductive adhesive is not conducive to subsequent use. That is, the raw material contains water, which reduces the storage stability and performance of the thermally conductive adhesive. In order to solve the above problems, the prepolymer and the inorganic filler are dehydrated before the reaction, thereby improving the storage stability of the thermally conductive adhesive.
[0026] The crosslinking agent is mixed with the dehydrated mixture, and heated and stirred under an inert atmosphere to obtain a mixed intermediate product. Specifically, in order to protect the system in which the crosslinking agent is mixed with the dehydrated mixture, the crosslinking agent is mixed with the dehydrated mixture under an inert atmosphere, and heated and stirred to obtain a mixed intermediate product. For example, inert gas protection can reduce the moisture in the air from entering the reaction system.
[0027] A catalyst is added to the mixed intermediate product, and the mixture is heated and stirred to obtain a thermal conductive adhesive. In order to promote further reaction, a catalyst is added to the mixed intermediate product, and the mixture is heated and stirred to obtain a thermal conductive adhesive.
[0028] Optionally, in the step of mixing the crosslinking agent with the dehydrated mixture, heating and stirring under an inert atmosphere to obtain a mixed intermediate product, the stirring method includes stirring with a dispersion disk;
[0029] And / or, in the step of adding the catalyst to the mixed intermediate product, heating and stirring to obtain the thermally conductive adhesive, the stirring method includes stirring with a dispersion disk.
[0030] In the present application, in addition to using a dispersion disk stirring (stirring speed of 300rpm to 2000rpm) in the process of dispersing the inorganic filler, a dispersion disk stirring (stirring speed of 300rpm to 2000rpm) can also be used in other stirring steps. Of course, other stirring methods, such as stirring paddles, etc., can also be used. That is, considering that the effective dispersion of the inorganic filler has been achieved in the process of dispersing the inorganic filler, then in the subsequent stirring process, the stirring method can be selectively selected. For example, in the step of mixing the crosslinking agent with the dehydrated mixture, heating and stirring in an inert atmosphere to obtain a mixed intermediate product, the stirring method can include dispersion disk stirring; in the step of adding a catalyst to the mixed intermediate product, heating and stirring to obtain a thermal conductive adhesive, the stirring method includes dispersion disk stirring.
[0031] Optionally, in the step of mixing the prepolymer and the inorganic filler and stirring and removing water through a dispersion disk to obtain a dehydrated mixture, the method further comprises:
[0032] The prepolymer and the inorganic filler are mixed and stirred by a dispersion plate, heated, and vacuumed to remove water.
[0033] In the process of dehydration, the water can be removed by heating and vacuuming. Of course, nitrogen can also be blown out during the process of vacuuming to remove water vapor.
[0034] Optionally, the heating temperature ranges from 120°C to 140°C;
[0035] And / or, the vacuum degree of the vacuum pumping ranges from -0.095 MPa to -0.1 MPa;
[0036] And / or, during the vacuum dehydration process, the dehydration time ranges from 2h to 5h;
[0037] And / or, after the vacuum removal of water, the total water content of the prepolymer and the inorganic filler is less than 0.1%.
[0038] In the dehydration process of the present application, the heating temperature range may include 120°C to 140°C.
[0039] The vacuum degree range of the vacuum extraction in the present application may include -0.095MPa to -0.1MPa.
[0040] In the process of vacuuming and removing water in the present application, the time range for removing water may include 2h to 5h.
[0041] After vacuuming and removing water, the total water content of the prepolymer and the inorganic filler is less than 0.1%. As mentioned above, considering that water will react with the isocyanate NCO group, the storage stability of the thermal conductive adhesive will deteriorate. Therefore, controlling the water content to less than 0.1% can improve the storage stability of the thermal conductive adhesive.
[0042] Optionally, before the step of mixing the prepolymer and the inorganic filler and stirring and removing water through a dispersion disk to obtain a dehydrated mixture, the method further comprises:
[0043] The prepolymer is preheated and melted; and / or the cross-linking agent is preheated and melted.
[0044] Before the reaction, the prepolymer and the cross-linking agent are preheated and melted respectively for use. In the corresponding feeding process, the corresponding molten raw materials are added in the form of liquid, which is conducive to a rapid fusion reaction.
[0045] Optionally, the formula components of the thermally conductive adhesive further include a tackifier, and in the step of mixing the prepolymer and the inorganic filler and stirring and dehydrating through a dispersion disk to obtain a dehydrated mixture, the following steps are further included:
[0046] The prepolymer, the inorganic filler and the thickener are mixed, stirred and dehydrated by a dispersion disk to obtain a dehydrated mixture.
[0047] The tackifier can further improve the adhesion of the thermal conductive adhesive. To this end, the prepolymer, the inorganic filler, and the tackifier are mixed and stirred and dehydrated through a dispersion disk to obtain a dehydrated mixture.
[0048] Optionally, before the step of mixing the cross-linking agent with the dehydrated mixture, heating and stirring under an inert atmosphere to obtain a mixed intermediate product, the method further comprises:
[0049] The temperature of the dehydrated mixture is controlled to be 15°C to 30°C lower than the polymerization temperature, and the polymerization temperature is 120°C to 130°C.
[0050] Considering that after the cross-linking agent (such as isocyanate compound) is added to the dehydrated mixture, the cross-linking agent will react with the prepolymer in the dehydrated mixture, and the reaction will generate heat, which will cause the temperature to rise by 15°C to 30°C. In order to control the reaction temperature within the polymerization temperature range, when the cross-linking agent (such as isocyanate compound) is added to the dehydrated mixture, the temperature of the dehydrated mixture is controlled to be 15°C to 30°C lower than the polymerization temperature, so that the temperature is maintained within the polymerization temperature range during the reaction, wherein the polymerization temperature is 120°C to 130°C.
[0051] Optionally, the formula components of the thermal conductive adhesive further include at least one of an antioxidant, an anti-ultraviolet absorber, and a coupling agent;
[0052] The step of adding the catalyst to the mixed intermediate product, heating and stirring to obtain the thermal conductive adhesive also includes:
[0053] The catalyst and at least one of the antioxidant, the anti-ultraviolet absorber and the coupling agent are added to the mixed intermediate product, heated, vacuumized and stirred to obtain a thermal conductive adhesive.
[0054] Antioxidants are organic compounds that can inhibit or delay the thermal oxidation of polymers and other organic compounds in the air, and improve the stability of thermal conductive adhesives. Anti-ultraviolet absorbers are used to improve the problem of reduced material performance caused by photochemical reactions of photosensitive substances in thermal conductive adhesives, such as photodegradation and photoaging. Coupling agents have inorganic compound-friendly groups and organic compound-friendly groups in their molecular structure. The coupling agents are hydrolyzed when they encounter residual water in the thermal conductive adhesive reaction system, and are grafted into the molecular chain of the thermal conductive adhesive after hydrolysis. The hydrolyzed alcohol small molecules will be drawn away during the vacuuming process, and the process of consuming water increases the storage stability of the thermal conductive adhesive. The performance of the thermal conductive adhesive is improved by adding at least one of antioxidants, anti-ultraviolet absorbers, and coupling agents to the reaction system.
[0055] For example, in one embodiment, during the process of adding a catalyst to the mixed intermediate product, an antioxidant, an anti-ultraviolet absorber, or a coupling agent may be added simultaneously; in another embodiment, two of the antioxidant, anti-ultraviolet absorber, and coupling agent may be added simultaneously, or an antioxidant, an anti-ultraviolet absorber, and a coupling agent may be added simultaneously.
[0056] In order to eliminate the bubbles generated during the reaction, vacuum stirring is used to remove the bubbles. It can be understood that the vacuum degree is lower than -0.095MPa.
[0057] Optionally, before the step of adding the catalyst to the mixed intermediate product and heating and stirring to obtain the thermal conductive adhesive, the method comprises:
[0058] The viscosity of the mixed intermediate product is tested. When the viscosity of the mixed intermediate product is in a range of 100,000 mPa.s to 170,000 mPa.s, the catalyst is added to the mixed intermediate product.
[0059] Considering that the viscosity of the mixed intermediate product ranges from 100,000 mPa.s to 170,000 mPa.s, the viscosity is still relatively low, which is conducive to dispersion, and when the viscosity is within the above range, the cross-linking agent has basically reacted completely, and a catalyst is needed to promote further reaction.
[0060] Optionally, after mixing the cross-linking agent with the dehydrated mixture, heating and stirring under an inert atmosphere to obtain a mixed intermediate product, the method further comprises:
[0061] The viscosity of the mixed intermediate product is tested at preset time intervals, preferably, the preset time comprises 0.5h to 1h.
[0062] In order to control the viscosity of the mixed intermediate product, the viscosity of the mixed intermediate product is tested at preset time intervals. At the same time, in order to effectively test the viscosity, the preset time includes 0.5h to 1h, that is, when the viscosity growth rate is faster, sampling and testing can be carried out every half hour; when the viscosity growth rate is slower, sampling and testing can be carried out every hour.
[0063] Optionally, the step of adding the catalyst to the mixed intermediate product, heating and stirring to obtain the thermal conductive adhesive comprises:
[0064] The catalyst is added to the mixed intermediate product, heated and stirred to obtain a mixed product, and the viscosity of the mixed product is tested. When the viscosity of the mixed product is in the range of 180,000 mPa.s to 200,000 mPa.s, heating is stopped to obtain a thermal conductive adhesive.
[0065] When the viscosity of the mixed product is in the range of 180,000 mPa.s to 200,000 mPa.s, the reaction is basically completed, and heating is stopped at this time to obtain a thermal conductive adhesive. This viscosity range is suitable for construction requirements.
[0066] In addition, the reaction endpoint can be controlled by testing the viscosity, thereby controlling the fluctuation between batches of prepared products and improving the batch stability of products.
[0067] That is, in the traditional preparation process, the material is directly discharged after the polymerization reaches the specified time, and the viscosity of each batch varies greatly. In addition, there are many factors that affect the viscosity of each batch, such as ambient temperature, humidity, heater temperature, vacuum degree, residues in the reactor, etc., all of which have a great impact on the polymerization of thermal conductive adhesive. Therefore, this application uses a rheometer to investigate the viscosity change of the thermal conductive adhesive raw material during the polymerization process, stops heating at a uniform viscosity range, and effectively controls the viscosity of the product.
[0068] Optionally, after adding the catalyst to the mixed intermediate product, heating and stirring to obtain a mixed product, and testing the viscosity of the mixed product, when the viscosity of the mixed product is in the range of 180,000 mPa.s to 200,000 mPa.s, heating is stopped to obtain the thermal conductive adhesive, the method further includes:
[0069] Within 1 hour after stopping heating, the thermal conductive adhesive package is discharged.
[0070] Thermally conductive adhesive (such as polyurethane type) is a moisture-curing reaction type adhesive. It cross-links and cures quickly after contacting moisture in the air. The curing process is irreversible. Therefore, moisture must be isolated as much as possible during the discharge process. And the adhesive just after discharge is in a fluid state, and it cannot be directly evacuated and packaged, otherwise the thermal conductivity will be irregular in the package. During the discharge process, nitrogen is filled for protection and the container is sealed for storage. Therefore, after stopping heating the container, it also includes: within 1 hour after stopping heating, the thermally conductive adhesive is packaged and discharged to improve the risk of contact with air.
[0071] In addition, it is necessary to clean the residual glue on the stirring equipment and the inner wall of the container while it is hot to ensure that the reactor is clean.
[0072] Optionally, the prepolymer comprises 41 to 90 parts, preferably, 65 to 75 parts;
[0073] And / or, the cross-linking agent comprises 7 to 15 parts, preferably, 9 to 13 parts;
[0074] And / or, the catalyst comprises 0.2 to 0.8 parts, preferably greater than 0.2 parts and less than or equal to 0.4 parts;
[0075] And / or, the inorganic filler includes a flame retardant, 5 to 10 parts, preferably, 8 to 10 parts;
[0076] And / or, the inorganic filler includes pigment, 1 to 3 parts, preferably greater than 1 part and less than or equal to 2 parts;
[0077] And / or, the formula components of the thermal conductive adhesive further include 5 to 10 parts of a tackifier, preferably 6 to 8 parts;
[0078] And / or, the formula components of the thermal conductive adhesive further include an antioxidant, 0.1 to 0.5 parts, preferably 0.2 to 0.4 parts;
[0079] And / or, the formula components of the thermal conductive adhesive further include an anti-ultraviolet absorber, 0.1 to 0.5 parts, preferably 0.2 to 0.4 parts;
[0080] And / or, the formula components of the thermal conductive adhesive also include a coupling agent, 0.5 to 1 part, preferably, 0.7 to 0.9 part.
[0081] The preparation method of the present application does not limit the number of parts of each formula component, which can be adjusted according to specific needs. For example, the prepolymer includes 41 to 90 parts, preferably 65 to 75 parts; and / or, the crosslinking agent includes 7 to 15 parts, preferably 9 to 13 parts; and / or, the catalyst includes 0.2 to 0.8 parts, preferably greater than 0.2 parts and less than or equal to 0.4 parts; and / or, the inorganic filler includes a flame retardant, 5 to 10 parts, preferably 8 to 10 parts; and / or, the inorganic filler includes a pigment, 1 to 3 parts, preferably The thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 5 parts and less than or equal to 10 parts, preferably, less than 6 parts and less than 8 ... more preferably, less than 6 parts and less than 8 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 5 parts and less than or equal to 10 parts, more preferably, less than 6 parts and less than 8 parts;
[0082] Optionally, the prepolymer comprises a hydroxyl-containing compound;
[0083] And / or, the cross-linking agent includes an isocyanate-based compound.
[0084] The present application does not limit the type of prepolymer, which may include, for example, a hydroxyl-containing compound. The present application does not limit the type of crosslinking agent, which may include, for example, an isocyanate-based compound.
[0085] Optionally, the hydroxyl-containing compound includes at least one of polyalkyl alcohol, polyether polyol, polyester polyol, alicyclic alcohol, aromatic alcohol, polytetrahydrofuran polyol, preferably includes at least one of polyalkyl alcohol, polyether polyol, polyester polyol;
[0086] And / or, the isocyanate compound includes at least one of diphenylmethane diisocyanate, 2,4-toluene diisocyanate, and toluene diisocyanate dimer;
[0087] And / or, the catalyst includes at least one of bismorpholinyl diethyl ether, dimethylcyclohexylamine, and N-methyldicyclohexylamine.
[0088] The hydroxyl-containing compounds of the present application include but are not limited to at least one of polyalkyl alcohols, polyether polyols, polyester polyols, alicyclic alcohols, aromatic alcohols, and polytetramethylene glycol, wherein the hydroxyl group provides a reactive unit that can react with an isocyanate group.
[0089] Preferably, at least one of polyalkyl alcohol, polyether polyol and polyester polyol is included. Polyalkyl alcohol has good flexibility and is a flexible segment in the polyurethane main chain, thereby improving the flexibility of the thermal conductive adhesive. The ether group and the ester group provide the polyurethane with flexibility and low temperature rheological resistance, so that it will not harden at low temperatures and lose its adhesive force.
[0090] The isocyanate-based compound of the present application includes, but is not limited to, at least one of diphenylmethane diisocyanate, 2,4-toluene diisocyanate, and toluene diisocyanate dimer.
[0091] The catalyst of the present application includes but is not limited to at least one of bismorpholinyl diethyl ether, dimethylcyclohexylamine, and N-methyldicyclohexylamine.
[0092] Optionally, the formula components of the thermal conductive adhesive further include a tackifier, and the tackifier includes at least one of acrylic resin, polyisobutylene, poly-n-butyl vinyl ether, methyl styrene and isobutylene copolymer, and ethylene propylene copolymer. Preferably, the tackifier includes acrylic resin, and the acrylic resin includes at least one of AC1920, AC1010, AC1021, AC1630, AC1632, AC1750, AC2740, and AC3820.
[0093] And / or, the inorganic filler includes a flame retardant, and the flame retardant includes at least one of magnesium hydroxide, aluminum hydroxide, and borate, and preferably, the surface of the flame retardant is modified with a hydrophobic substance;
[0094] and / or, the inorganic filler comprises a pigment, the pigment comprises at least one of magnesium oxide, zinc oxide, aluminum oxide, boron carbide, aluminum nitride, carbon black, graphite and carbon nanotubes, preferably, the surface of the pigment is modified with a hydrophobic substance;
[0095] And / or, the formula components of the thermal conductive adhesive further include an antioxidant, and the antioxidant includes at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 168, antioxidant Ultranox 626, and antioxidant PEPQ;
[0096] And / or, the formula components of the thermal conductive adhesive further include an anti-ultraviolet absorber, and the anti-ultraviolet absorber includes at least one of 2-(2'-hydroxyphenyl 3',5'-dipentylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, and 2-hydroxy-4-n-octyloxybenzophenone;
[0097] And / or, the formula components of the thermal conductive adhesive further include a coupling agent, and the coupling agent includes at least one of coupling agent 540, coupling agent 550, coupling agent 560, coupling agent 570, coupling agent 1189, and coupling agent 792.
[0098] The tackifier of the present application includes but is not limited to at least one of acrylic resin, polyisobutylene, poly-n-butyl vinyl ether, methyl styrene and isobutylene copolymer, and ethylene propylene copolymer. Preferably, it includes acrylic resin. The bonding strength of the thermal conductive adhesive mainly depends on the cohesive force of the thermal conductive adhesive and the physical bonding strength provided by the acrylic resin. After the thermal conductive adhesive is used, its bonding strength increases, which mainly depends on the cross-linking and curing of NCO in the adhesive with moisture. After a period of curing, it is completely cured. Acrylic resin includes but is not limited to at least one of AC1920, AC1010, AC1021, AC1630, AC1632, AC1750, AC2740, and AC3820.
[0099] The flame retardant in the present application includes but is not limited to at least one of magnesium hydroxide, aluminum hydroxide, and borate. Preferably, the surface of the flame retardant is modified with a hydrophobic substance. By modifying the surface of the flame retardant with a hydrophobic substance, the dispersibility of the flame retardant in the reaction system can be improved. It can be understood that before the inorganic flame retardant is hydrophobically modified, it is easy to agglomerate, and the agglomeration will cause the thermal conductive adhesive to have particles. The present application uses a hydrophobic substance to modify the surface of the inorganic flame retardant to improve its dispersibility and reduce agglomeration, thereby reducing the phenomenon of particles in the thermal conductive adhesive. After the surface of the inorganic flame retardant is hydrophobically modified, the surface may have organic functional groups, so that the flame retardant can be cross-linked to the organic skeleton of the thermal conductive adhesive, thereby improving the dispersibility and compatibility of the inorganic flame retardant in the thermal conductive adhesive. 。 Furthermore, the flame retardant modifies the hydrophobic substance, making it difficult for the flame retardant to absorb water, improving the flame retardant to bring moisture into the reaction system, thereby reducing the premature curing of the thermal conductive adhesive by moisture, improving the problem of shortening the storage period of the thermal conductive adhesive, and improving the thixotropy of the thermal conductive adhesive, facilitating the stirring and coating of the thermal conductive adhesive.
[0100] The pigments in the present application include but are not limited to at least one of magnesium oxide, zinc oxide, aluminum oxide, boron carbide, aluminum nitride, carbon black, graphite and carbon nanotubes. Preferably, the surface of the pigment is modified with a hydrophobic substance. By modifying the surface of the pigment with a hydrophobic substance, the dispersibility of the pigment in the reaction system can be improved, the agglomeration of the pigment can be reduced, and the phenomenon of particles appearing in the thermal conductive adhesive can be reduced.
[0101] In addition, materials such as magnesium oxide, carbon black, graphite and carbon nanotubes in the pigment are also thermally conductive.
[0102] It is understood that the surface-modified hydrophobic substance in the present application can be a surfactant or a silane coupling agent, and there is no specific limitation. For example, in one embodiment, the specific treatment agent can include an aqueous solution of a silane coupling agent or an alcohol solution of a stearate, and the aqueous solution of a silane coupling agent or the alcohol solution of a stearate is sprayed onto the surface of the material at a high temperature, stirred, and vacuum-activated for modification. For example, in the modification process, the amount of the silane coupling agent is selected to be 0.5% to 1.5% of the mass of the pigment or the mass of the inorganic flame retardant compound, and an addition amount of 1% is more suitable for most applications.
[0103] The antioxidant in the present application includes but is not limited to at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 168, antioxidant Ultranox 626, and antioxidant PEPQ.
[0104] The anti-ultraviolet absorber in the present application includes but is not limited to at least one of 2-(2'-hydroxyphenyl 3',5'-dipentylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, and 2-hydroxy-4-n-octyloxybenzophenone.
[0105] The coupling agent in the present application includes but is not limited to at least one of coupling agent 540 , coupling agent 550 , coupling agent 560 , coupling agent 570 , coupling agent 1189 , and coupling agent 792 .
[0106] Optionally, the hydroxyl-containing compound includes polyalkyl alcohol, polyether polyol, polyester polyol, the polyalkyl alcohol includes 20 to 40 parts, preferably, 25 to 35 parts, the polyether polyol includes 20 to 40 parts, preferably, 25 to 35 parts, the polyester polyol includes 1 to 10 parts, preferably, 3 to 6 parts;
[0107] And / or, the hydroxyl-containing compound comprises a polyalkyl alcohol, the polyalkyl alcohol comprises at least one of polypropylene glycol and polyethylene glycol, preferably comprises polypropylene glycol, and the molecular weight of the polypropylene glycol comprises 800 to 4000;
[0108] And / or, the hydroxyl-containing compound comprises a polyether polyol, the polyether polyol comprises at least one of polytetramethylene ether glycol, a polyether polyol initiated by sucrose and glycerol, a toluene diamine polyether polyol, and a sorbitol polyether polyol, preferably comprises polytetramethylene ether glycol, and the molecular weight range of the polytetramethylene ether glycol comprises 1000 to 8000, preferably, 1000 to 3000;
[0109] And / or, the hydroxyl-containing compound includes polyester polyol, the polyester polyol includes crystalline polyester polyol, and the crystalline polyester polyol includes at least one of polyester DC7380, polyester DC7360, polyester DC7320, and polyester DC7130.
[0110] The hydroxyl-containing compounds of the present application include polyalkyl alcohols, polyether polyols, and polyester polyols. The polyalkyl alcohols include 20 to 40 parts, preferably 25 to 35 parts, the polyether polyols include 20 to 40 parts, preferably 25 to 35 parts, and the polyester polyols include 1 to 10 parts, preferably 3 to 6 parts. The above-mentioned hydroxyl-containing compounds within the above-mentioned range can improve the flexibility and low-temperature rheological resistance of the polyurethane.
[0111] The hydroxyl-containing compound includes polyalkyl alcohol, which includes but is not limited to at least one of polypropylene glycol and polyethylene glycol. Preferably, it includes polypropylene glycol, and the molecular weight of polypropylene glycol is 800 to 4000; polypropylene glycol can improve the fluidity of the thermal conductive adhesive, and the molecular weight has fluidity within a suitable range, thereby improving the processing performance of the thermal conductive adhesive.
[0112] The hydroxyl-containing compound includes, but is not limited to, polyether polyols, which include at least one of polytetramethylene ether glycol, polyether polyols initiated by sucrose and glycerol, toluene diamine polyether polyols, and sorbitol polyether polyols, preferably, polytetramethylene ether glycol, and the molecular weight range of polytetramethylene ether glycol includes 1000 to 8000, preferably, 1000 to 3000. , Polytetramethylene ether glycol can improve the flexibility of thermal conductive adhesive.
[0113] The hydroxyl-containing compound includes polyester polyols, and the polyester polyols include crystalline polyester polyols, and the crystalline polyester polyols include at least one of polyester DC7380, polyester DC7360, polyester DC7320, and polyester DC7130. Crystalline polyester polyols can improve the high and low temperature resistance of the thermal conductive adhesive. It can be understood that the crystalline polyester polyols will melt into a liquid state during the temperature increase process, absorbing heat at this time, and the crystalline polyester polyols will release heat during the temperature reduction process, and the molecular chains will be rearranged to form crystals, that is, when the polyurethane material receives external temperature changes, the crystalline polyester polyols can absorb or release heat (when the temperature of the polyurethane increases, the crystalline polyester polyols absorb heat, and when the temperature of the polyurethane decreases, the crystalline polyester polyols release heat), so that the polyurethane has the characteristics of high and low temperature resistance.
[0114] It is understandable that the hydroxyl-containing compound can include at least two of polyester DC7380, polyester DC7360, polyester DC7320, and polyester DC7130 at the same time, and both polyester with high glass transition temperature and polyester with low glass transition temperature are selected to improve the high temperature and low temperature resistance of the thermal conductive adhesive material. Due to different molecular structures and segment structures, the high temperature and low temperature resistance range caused by the difference in glass transition temperature will be widened, and the high glass transition temperature has high temperature resistance, and the low glass transition temperature has low temperature resistance.
[0115] The present application also provides a battery, which includes the thermal conductive adhesive, or includes the thermal conductive adhesive prepared by the preparation method of the thermal conductive adhesive.
[0116] The present application also provides an electrical device, which includes the battery as described above.
[0117] The preparation method of the thermal conductive adhesive of the present application includes: preparing the formula components of the thermal conductive adhesive, the formula components of the thermal conductive adhesive include prepolymers, cross-linking agents, catalysts, and inorganic fillers; heating and stirring the formula components to obtain the thermal conductive adhesive, the stirring method includes stirring with a dispersion disk, and the stirring speed ranges from 300rpm to 2000rpm. In the process of preparing the thermal conductive adhesive, the present application adopts dispersion disk stirring, and the stirring speed ranges from 300rpm to 2000rpm. Mechanical shearing is performed by means of the high-speed flow field of the dispersion disk to obtain a uniform and fine thermal conductive adhesive, thereby improving the dispersibility of the inorganic filler and thus improving the adhesion of the thermal conductive adhesive. BRIEF DESCRIPTION OF THE DRAWINGS
[0118] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0119] Figure 1 A schematic diagram of a process for preparing a thermally conductive adhesive according to an embodiment of the present application;
[0120] Figure 2 This is a dispersion disk according to Example 1 of the present application.
[0121] Description of Figure Numbers:
[0122] Label name Label name 100 Dispersion disc 2 Through-hole 1 Dispersion disc body 3 Dispersed teeth
[0123] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0124] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0125] Hereinafter, the thermal conductive adhesive and its preparation method, battery and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0126] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0127] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0128] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0129] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0130] Thermally conductive adhesive has the function of conducting heat. For example, a heat-generating device will generate heat, which can be dissipated through thermal conductive adhesive.
[0131] For example, power batteries generate a lot of heat during the charging and discharging process, and the heat needs to be dissipated as quickly as possible. In low-temperature environments, they need to be heated to transfer the heat to the inside of the battery. The performance of power batteries can be improved by filling thermal conductive glue between the battery heat dissipation surface and the cooling system.
[0132] Considering that in the preparation process of thermal conductive adhesive, there may be a phenomenon that particles appear in the prepared thermal conductive adhesive due to uneven dispersion of inorganic fillers and agglomeration of inorganic fillers, the presence of particles in the thermal conductive adhesive will reduce the viscosity of the thermal conductive adhesive.
[0133] In order to improve the above problems, the present application provides a method for preparing a thermally conductive adhesive, comprising: preparing formula components of the thermally conductive adhesive, the formula components of the thermally conductive adhesive including a prepolymer, a cross-linking agent, a catalyst, and an inorganic filler; heating and stirring the formula components to obtain the thermally conductive adhesive, the stirring method including stirring with a dispersion disk, and the stirring speed ranges from 300 rpm to 2000 rpm.
[0134] Dispersing disc is an accessory for high-speed disperser, connected to the main shaft of high-speed disperser. When the main shaft of disperser runs at high speed, the dispersing disc rotates and forms a turbulent zone at the edge.
[0135] The dispersing disc is provided with dispersing teeth. It is understood that the toothed dispersing disc is a type of vortex agitator. The outer edge of the dispersing disc is serrated. The shearing performance is very high under high-speed rotation, and the breaking and crushing effect is strong. It is suitable for dispersing and mixing of two phases with large differences in physical properties, such as the dispersion process of coatings. The applicable speed of the toothed dispersing disc is very high, much higher than that of the paddle agitator. During the high-speed rotation process, the dispersing teeth of the dispersing disc shear, crush and disperse the material multiple times, thereby breaking up and mixing the agglomerated particles in the slurry to achieve uniform mixing of the slurry.
[0136] The dispersion disc is provided with dispersion teeth. The present application does not limit the shape of the dispersion teeth, the location of the dispersion teeth on the dispersion disc, and the number of the dispersion teeth; for example, a peripheral tooth dispersion disc, an internal tooth dispersion disc, a single-layer dispersion disc, a multi-layer dispersion disc, etc. can be tried.
[0137] It is also understandable that the diameter of the dispersion disk will affect the stirring effect. Generally speaking, the diameter of the dispersion disk is 0.3 to 0.7 of the diameter of the mixing barrel.
[0138] as follows Figure 2 , which is a schematic structural diagram of a dispersion disk 100. The dispersion disk 100 includes a dispersion disk body 1 and dispersion teeth 3 arranged on the dispersion disk body 1. A shaft through hole 2 is also arranged in the middle thereof for mounting the dispersion disk on the rotating shaft.
[0139] Prepolymer and crosslinking agent, the structure of prepolymer includes functional groups that can react with crosslinking agent, so that prepolymer and crosslinking agent react. For example, prepolymer includes hydroxyl-containing compound, crosslinking agent includes isocyanate compound, and the two react to generate polyurethane. The reaction formula is as follows
[0140]
[0141] A catalyst is a substance that can change the rate of a chemical reaction without being consumed itself, such as dimorpholinodiethyl ether.
[0142] Inorganic fillers, inorganic substances, including but not limited to pigments, thermal conductors, flame retardants, etc.
[0143] Considering that in the preparation process of thermal conductive adhesive, there will be uneven dispersion of inorganic fillers and agglomeration of inorganic fillers, which will cause the prepared thermal conductive adhesive to have particles, thereby causing a decrease in adhesion. Specifically, unevenly dispersed inorganic fillers will cause agglomerates and gels, causing stress concentration and damage during the tensile shear process, reducing the shear resistance of the bond. Agglomerates and gels inhibit the interaction between the adhesive components in the thermal conductive adhesive and the inorganic fillers, thereby reducing the cohesion (adhesion) of the adhesive, causing a decrease in adhesion and shear force.
[0144] For example, inorganic fillers include but are not limited to inorganic pigments or inorganic flame retardants. These substances have soft agglomerate and hard agglomerate particles. It can be understood that soft agglomerate refers to the agglomeration formed by short-range surface forces such as electrostatic attraction, van der Waals force or capillary force between primary particles, and hard agglomerate refers to the existence of chemical bonds in addition to the van der Waals force and Coulomb force between particles in the hard agglomerate.
[0145] For example, when the thermal conductive adhesive formula is dehydrated or polymerized at a certain temperature, it cannot provide corresponding self-shearing force. The inorganic fillers in the thermal conductive adhesive formula (such as inorganic minerals, including but not limited to calcium carbonate, talc, zinc borate, magnesium hydroxide, aluminum hydroxide, magnesium oxide, aluminum oxide, boron nitride, etc.) are particles with soft agglomerates and hard agglomerates and cannot be effectively dispersed in the thermal conductive adhesive formula.
[0146] In order to solve the above problems, the present application adopts a stirring method of a dispersion disk, and at a certain rotation speed (300rpm to 2000rpm), mechanical shearing is performed by relying on the high-speed flow field of the dispersion disk to obtain a uniform and delicate thermal conductive adhesive.
[0147] It can be understood that the present application adopts dispersion disk stirring in the preparation process, and the stirring speed range is 300rpm to 2000rpm. The disk surface of the dispersion disk is provided with dispersion teeth. When running at high speed, the dispersion disk is in a rotating state. At the same time, a turbulent zone will be formed at the edge of the dispersion teeth to accelerate the mixing and mechanical shearing of the materials. In addition, when the speed is in the range of 300rpm to 2000rpm, no particles appear. If a stirring paddle, stirring rod, etc. are used, the speed will still be generated when the speed is in the range of 300rpm to 2000rpm. This is mainly because even if the speed is faster, based on the fact that the stirring paddle and stirring rod have no dispersion teeth, the mechanical shearing effect of the material is not as good as that of a dispersion disk, which still leads to the generation of particles.
[0148] It is also understandable that the particles present in the thermally conductive adhesive will cause the adhesive force of the thermally conductive adhesive to decrease. Specifically, unevenly dispersed inorganic fillers will cause agglomerates and gels, resulting in stress concentration and damage during the tensile shear process, reducing the shear resistance of the bond. Agglomerates and gels inhibit the interaction between the adhesive components in the thermally conductive adhesive and the inorganic fillers, thereby reducing the cohesion (adhesion) of the adhesive, causing a decrease in adhesion and shear force. The present application improves the adhesion of the thermally conductive adhesive by using a dispersion disk for stirring during the preparation process, at a certain speed, to increase the dispersibility of the inorganic filler.
[0149] In the present application, the types of prepolymer and cross-linking agent are not specifically limited. For example, when the thermal conductive adhesive is of polyurethane type, the prepolymer includes a hydroxyl-containing compound, and the cross-linking agent includes an isocyanate-containing compound.
[0150] In addition, the present application adopts a single-component preparation process during the preparation process. Compared with the need to prepare component A and component B separately and then mix components A and B to prepare the thermal conductive adhesive, the preparation method of the present application is simpler.
[0151] In the above-mentioned 300rpm to 2000rpm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 300rpm, 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm, 1200rpm, 1400rpm, 1600rpm, 1800rpm, 2000rpm, etc., as well as the range values between any two of the above-mentioned point values.
[0152] In one embodiment, during the heating and stirring of the formulation components, the stirring speed ranges from 600 rpm to 1000 rpm.
[0153] It is understandable that increasing the rotation speed can improve the phenomenon of particle generation. Considering the equipment cost issue, for example, the higher the rotation speed, the higher the requirements for the equipment, and the higher the cost and maintenance requirements of the equipment. Therefore, in the process of heating and stirring the formula components, the stirring speed can range from 600rpm to 1000rpm.
[0154] In the above 600rpm to 1000rpm, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm, etc., as well as the range values between any two of the above point values.
[0155] In one embodiment, the step of heating and stirring the formula components to obtain the thermally conductive adhesive includes: mixing the prepolymer and the inorganic filler, stirring and dehydrating through a dispersion disk to obtain a dehydrated mixture; mixing the crosslinking agent with the dehydrated mixture, heating and stirring under an inert atmosphere to obtain a mixed intermediate product; adding the catalyst to the mixed intermediate product, heating and stirring to obtain the thermally conductive adhesive.
[0156] In the process of heating and stirring the formulation components, the prepolymer and the inorganic filler are mixed and stirred and dehydrated by a dispersion disk to obtain a dehydrated mixture; that is, the prepolymer and the inorganic filler are mixed by a dispersion disk at a stirring speed of 300 rpm to 2000 rpm, which can effectively disperse the inorganic filler.
[0157] At the same time, considering that the raw material contains water, which will cure the thermally conductive adhesive prematurely, that is, during the storage of the thermally conductive adhesive, the water in the thermally conductive adhesive will react with the isocyanate group (NCO) in the thermally conductive adhesive (for example, taking the cross-linking agent as an isocyanate compound as an example), thereby curing the thermally conductive adhesive and reducing the storage stability of the thermally conductive adhesive. In addition, the cured thermally conductive adhesive is not conducive to subsequent use. That is, the raw material contains water, which reduces the storage stability and performance of the thermally conductive adhesive. In order to solve the above problems, the prepolymer and the inorganic filler are dehydrated before the reaction, thereby improving the storage stability of the thermally conductive adhesive.
[0158] The crosslinking agent is mixed with the dehydrated mixture, and heated and stirred under an inert atmosphere to obtain a mixed intermediate product. Specifically, in order to protect the system in which the crosslinking agent is mixed with the dehydrated mixture, the crosslinking agent is mixed with the dehydrated mixture under an inert atmosphere, and heated and stirred to obtain a mixed intermediate product. For example, inert gas protection can reduce the moisture in the air from entering the reaction system.
[0159] A catalyst is added to the mixed intermediate product, and the mixture is heated and stirred to obtain a thermal conductive adhesive. In order to promote further reaction, a catalyst is added to the mixed intermediate product, and the mixture is heated and stirred to obtain a thermal conductive adhesive.
[0160] In one embodiment, in the step of mixing the cross-linking agent with the dehydrated mixture, heating and stirring under an inert atmosphere to obtain a mixed intermediate product, the stirring method includes stirring with a dispersion disk; and / or, in the step of adding the catalyst to the mixed intermediate product, heating and stirring to obtain a thermally conductive adhesive, the stirring method includes stirring with a dispersion disk.
[0161] In the present application, in addition to using a dispersion disk stirring (stirring speed of 300rpm to 2000rpm) in the process of dispersing the inorganic filler, a dispersion disk stirring (stirring speed of 300rpm to 2000rpm) can also be used in other stirring steps. Of course, other stirring methods, such as stirring paddles, etc., can also be used. That is, considering that the effective dispersion of the inorganic filler has been achieved in the process of dispersing the inorganic filler, then in the subsequent stirring process, the stirring method can be selectively selected. For example, in the step of mixing the crosslinking agent with the dehydrated mixture, heating and stirring in an inert atmosphere to obtain a mixed intermediate product, the stirring method can include dispersion disk stirring; in the step of adding a catalyst to the mixed intermediate product, heating and stirring to obtain a thermal conductive adhesive, the stirring method includes dispersion disk stirring.
[0162] In one embodiment, the step of mixing the prepolymer and the inorganic filler, stirring and removing water through a dispersion disk to obtain a dehydrated mixture further includes: mixing the prepolymer and the inorganic filler, stirring and heating through a dispersion disk, and vacuuming to remove water.
[0163] In the process of dehydration, the water can be removed by heating and vacuuming. Of course, nitrogen can also be blown out during the process of vacuuming to remove water vapor.
[0164] In one embodiment, the heating temperature ranges from 120°C to 140°C; and / or the vacuum degree ranges from -0.095MPa to -0.1MPa; and / or, during the vacuum dehydration process, the dehydration time ranges from 2h to 5h; and / or, after the vacuum dehydration, the total water content of the prepolymer and the inorganic filler is less than 0.1%.
[0165] In the dehydration process of the present application, the heating temperature range may include 120°C to 140°C.
[0166] The vacuum degree range of the vacuum extraction in the present application may include -0.095MPa to -0.1MPa.
[0167] In the process of vacuuming and removing water in the present application, the time range for removing water may include 2h to 5h.
[0168] After vacuuming and removing water, the total water content of the prepolymer and the inorganic filler in the present application is less than 0.1%. As mentioned above, considering that water will react with the isocyanate NCO group, the storage stability of the thermal conductive adhesive will deteriorate. Therefore, controlling the water content to less than 0.1% can improve the storage stability of the thermal conductive adhesive.
[0169] In the above-mentioned 120℃ to 140℃, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 120℃, 122℃, 125℃, 128℃, 130℃, 132℃, 135℃, 138℃, 140℃, etc., and the range values between any two of the above-mentioned point values.
[0170] In the above-mentioned -0.095MPa to -0.1MPa, the values include the minimum and maximum values of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and -0.095MPa, -0.096MPa, -0.097MPa, -0.098MPa, -0.099MPa, -0.1MPa, etc., as well as the range values between any two of the above-mentioned point values.
[0171] In the above 2h to 5h, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 2h, 3h, 4h, 5h, etc., and the range values between any two of the above point values.
[0172] In the above-mentioned less than 0.1%, the values include the minimum and maximum values of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 0%, 0.001%, 0.002%, 0.005%, 0.01%, 0.003%, 0.006%, 0.007%, 0.09%, etc., and the range values between any two of the above-mentioned point values.
[0173] In one embodiment, before the step of mixing the prepolymer and the inorganic filler and stirring and removing water through a dispersion disk to obtain a dehydrated mixture, the method further includes: preheating and melting the prepolymer; and / or preheating and melting the crosslinking agent.
[0174] Before the reaction, the prepolymer and the cross-linking agent are preheated and melted respectively for use. In the corresponding feeding process, the corresponding molten raw materials are added in the form of liquid, which is conducive to a rapid fusion reaction.
[0175] In one embodiment, the formula components of the thermally conductive adhesive also include a tackifier. In the step of mixing the prepolymer and the inorganic filler, stirring and dehydrating through a dispersion disk to obtain a dehydrated mixture, it also includes: mixing the prepolymer, the inorganic filler, and the tackifier, stirring and dehydrating through a dispersion disk to obtain a dehydrated mixture.
[0176] The tackifier can further improve the adhesion of the thermal conductive adhesive. To this end, the prepolymer, the inorganic filler, and the tackifier are mixed and stirred and dehydrated through a dispersion disk to obtain a dehydrated mixture.
[0177] In one embodiment, before the step of mixing the crosslinking agent with the dehydrated mixture, heating and stirring under an inert atmosphere to obtain a mixed intermediate product, it also includes: controlling the temperature of the dehydrated mixture to be 15°C to 30°C lower than the polymerization temperature, and the polymerization temperature is 120°C to 130°C.
[0178] Considering that after the cross-linking agent (such as isocyanate compound) is added to the dehydrated mixture, the cross-linking agent will react with the prepolymer in the dehydrated mixture, and the reaction will generate heat, which will cause the temperature to rise by 15°C to 30°C. In order to control the reaction temperature within the polymerization temperature range, when the cross-linking agent (such as isocyanate compound) is added to the dehydrated mixture, the temperature of the dehydrated mixture is controlled to be 15°C to 30°C lower than the polymerization temperature, so that the temperature is maintained within the polymerization temperature range during the reaction, wherein the polymerization temperature is 120°C to 130°C.
[0179] In the above-mentioned 15℃ to 30℃, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 15℃, 18℃, 20℃, 22℃, 23℃, 24℃, 25℃, 26℃, 27℃, 28℃, 29℃, 30℃, etc., and the range values between any two of the above-mentioned point values.
[0180] In the above-mentioned 120℃ to 130℃, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 120℃, 121℃, 122℃, 123℃, 124℃, 125℃, 126℃, 127℃, 128℃, 129℃, 130℃, etc., and the range values between any two of the above-mentioned point values.
[0181] In one embodiment, the formula components of the thermally conductive adhesive also include at least one of an antioxidant, an anti-ultraviolet absorber, and a coupling agent; in the step of adding the catalyst to the mixed intermediate product, heating and stirring to obtain the thermally conductive adhesive, it also includes: adding the catalyst and at least one of the antioxidant, the anti-ultraviolet absorber, and the coupling agent to the mixed intermediate product, heating, vacuuming and stirring to obtain the thermally conductive adhesive.
[0182] Antioxidants are organic compounds that can inhibit or delay the thermal oxidation of polymers and other organic compounds in the air, and improve the stability of thermal conductive adhesives. Anti-ultraviolet absorbers are used to improve the problem of reduced material performance caused by photochemical reactions of photosensitive substances in thermal conductive adhesives, such as photodegradation and photoaging. Coupling agents have inorganic compound-friendly groups and organic compound-friendly groups in their molecular structure. The coupling agents are hydrolyzed when they encounter residual water in the thermal conductive adhesive reaction system, and are grafted into the molecular chain of the thermal conductive adhesive after hydrolysis. The hydrolyzed alcohol small molecules will be drawn away during the vacuuming process, and the process of consuming water increases the storage stability of the thermal conductive adhesive. The performance of the thermal conductive adhesive is improved by adding at least one of antioxidants, anti-ultraviolet absorbers, and coupling agents to the reaction system.
[0183] For example, in one embodiment, during the process of adding a catalyst to the mixed intermediate product, an antioxidant, an anti-ultraviolet absorber, or a coupling agent may be added simultaneously; in another embodiment, two of the antioxidant, anti-ultraviolet absorber, and coupling agent may be added simultaneously, or an antioxidant, an anti-ultraviolet absorber, and a coupling agent may be added simultaneously.
[0184] In order to eliminate the bubbles generated during the reaction, vacuum stirring is used to remove the bubbles. It can be understood that the vacuum degree is lower than -0.095MPa.
[0185] In one embodiment, before the step of adding the catalyst to the mixed intermediate product and heating and stirring to obtain the thermal conductive adhesive, the step includes: testing the viscosity of the mixed intermediate product, and adding the catalyst to the mixed intermediate product when the viscosity of the mixed intermediate product is in the range of 100,000 mPa.s to 170,000 mPa.s.
[0186] Considering that the viscosity of the mixed intermediate product ranges from 100,000 mPa.s to 170,000 mPa.s, the viscosity is still relatively low, which is conducive to dispersion, and when the viscosity is within the above range, the cross-linking agent has basically reacted completely, and a catalyst is needed to promote further reaction.
[0187] In the above-mentioned 100,000 mPa.s to 170,000 mPa.s, the values include the minimum and maximum values of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 100,000 mPa.s, 110,000 mPa.s, 120,000 mPa.s, 130,000 mPa.s, 140,000 mPa.s, 150,000 mPa.s, 160,000 mPa.s, 170,000 mPa.s, etc., as well as the range values between any two of the above-mentioned point values.
[0188] In one embodiment, after the cross-linking agent and the dehydrated mixture are mixed, heated and stirred under an inert atmosphere to obtain a mixed intermediate product, the process further comprises: testing the viscosity of the mixed intermediate product at preset time intervals, preferably, the preset time includes 0.5h to 1h.
[0189] In order to control the viscosity of the mixed intermediate product, the viscosity of the mixed intermediate product is tested at preset time intervals. At the same time, in order to effectively test the viscosity, the preset time includes 0.5h to 1h, that is, when the viscosity growth rate is faster, sampling and testing can be carried out every half hour; when the viscosity growth rate is slower, sampling and testing can be carried out every hour.
[0190] In the above 0.5h to 1h, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, etc., and the range values between any two of the above point values.
[0191] In one embodiment, the step of adding the catalyst to the mixed intermediate product, heating and stirring to obtain the thermal conductive adhesive includes: adding the catalyst to the mixed intermediate product, heating and stirring to obtain a mixed product, and testing the viscosity of the mixed product. When the viscosity range of the mixed product is between 180,000 mPa.s and 200,000 mPa.s, heating is stopped to obtain the thermal conductive adhesive.
[0192] When the viscosity of the mixed product is in the range of 180,000 mPa.s to 200,000 mPa.s, the reaction is basically completed, and heating is stopped at this time to obtain a thermal conductive adhesive. This viscosity range is suitable for construction requirements.
[0193] In addition, the reaction endpoint can be controlled by testing the viscosity, thereby controlling the fluctuation between batches of prepared products and improving the batch stability of products.
[0194] That is, in the traditional preparation process, the material is directly discharged after the polymerization reaches the specified time, and the viscosity of each batch varies greatly. In addition, there are many factors that affect the viscosity of each batch, such as ambient temperature, humidity, heater temperature, vacuum degree, residues in the reactor, etc., all of which have a great impact on the polymerization of thermal conductive adhesive. Therefore, this application uses a rheometer to investigate the viscosity change of the thermal conductive adhesive raw material during the polymerization process, stops heating at a uniform viscosity range, and effectively controls the viscosity of the product.
[0195] In the above-mentioned 180,000 mPa.s to 200,000 mPa.s, the values include the minimum and maximum values of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 180,000 mPa.s, 185,000 mPa.s, 190,000 mPa.s, 195,000 mPa.s, 200,000 mPa.s, etc., as well as the range values between any two of the above-mentioned point values.
[0196] In one embodiment, after adding the catalyst to the mixed intermediate product, heating and stirring to obtain a mixed product, and testing the viscosity of the mixed product, when the viscosity of the mixed product is in the range of 180,000 mPa.s to 200,000 mPa.s, heating is stopped to obtain the thermal conductive adhesive, the method further includes:
[0197] Within 1 hour after stopping heating, the thermal conductive adhesive package is discharged.
[0198] Thermally conductive adhesive (such as polyurethane type) is a moisture-curing reaction type adhesive. It cross-links and cures quickly after contacting moisture in the air. The curing process is irreversible. Therefore, moisture must be isolated as much as possible during the discharge process. And the adhesive just after discharge is in a fluid state, and it cannot be directly evacuated and packaged, otherwise the thermal conductivity will be irregular in the package. During the discharge process, nitrogen is filled for protection and the container is sealed for storage. Therefore, after stopping heating the container, it also includes: within 1 hour after stopping heating, the thermally conductive adhesive is packaged and discharged to improve the risk of contact with air.
[0199] In addition, it is necessary to clean the residual glue on the stirring equipment and the inner wall of the container while it is hot to ensure that the reactor is clean.
[0200] In one embodiment, the prepolymer includes 41 to 90 parts, preferably 65 to 75 parts; and / or, the crosslinking agent includes 7 to 15 parts, preferably 9 to 13 parts; and / or, the catalyst includes 0.2 to 0.8 parts, preferably greater than 0.2 parts and less than or equal to 0.4 parts; and / or, the inorganic filler includes a flame retardant, 5 to 10 parts, preferably 8 to 10 parts; and / or, the inorganic filler includes a pigment, 1 to 3 parts, preferably greater than 1 part and less than or equal to 2 parts; And / or, the formula components of the thermally conductive adhesive also include a tackifier, 5 to 10 parts, preferably 6 to 8 parts; and / or, the formula components of the thermally conductive adhesive also include an antioxidant, 0.1 to 0.5 parts, preferably 0.2 to 0.4 parts; and / or, the formula components of the thermally conductive adhesive also include an anti-ultraviolet absorber, 0.1 to 0.5 parts, preferably 0.2 to 0.4 parts; and / or, the formula components of the thermally conductive adhesive also include a coupling agent, 0.5 to 1 parts, preferably 0.7 to 0.9 parts.
[0201] The preparation method of the present application does not limit the number of parts of each formula component, which can be adjusted according to specific needs. For example, the prepolymer includes 41 to 90 parts, preferably 65 to 75 parts; and / or, the crosslinking agent includes 7 to 15 parts, preferably 9 to 13 parts; and / or, the catalyst includes 0.2 to 0.8 parts, preferably greater than 0.2 parts and less than or equal to 0.4 parts; and / or, the inorganic filler includes a flame retardant, 5 to 10 parts, preferably 8 to 10 parts; and / or, the inorganic filler includes a pigment, 1 to 3 parts, preferably The thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 1 part and less than or equal to 2 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 5 parts and less than or equal to 10 parts, preferably, less than 6 parts and less than 8 ... more preferably, less than 6 parts and less than 8 parts; and / or, the thermal conductive adhesive may be used in an amount greater than 5 parts and less than or equal to 10 parts, more preferably, less than 6 parts and less than 8 parts;
[0202] In the above 41 to 90 parts, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 41, 43, 45, 47, 50, 51, 53, 55, 57, 60, 61, 63, 65, 67, 70, 71, 73, 75, 77, 80, 81, 83, 85, 87, 90, etc., and the range values between any two of the above point values.
[0203] Among the above 7 to 15 parts, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 7, 8, 9, 10, 11, 12, 13, 14, 15, etc., and the range values between any two of the above point values.
[0204] In the above 0.2 to 0.8 parts, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, etc., as well as the range values between any two of the above point values.
[0205] Among the above 5 to 10 parts, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 5, 6, 7, 8, 9, 10, etc., as well as the range values between any two of the above point values.
[0206] In the above-mentioned 1 to 3 parts, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 1, 2, 3, etc., as well as the range values between any two of the above-mentioned point values.
[0207] In the above 0.1 to 0.5 parts, the values include the minimum and maximum values of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values in the embodiments and 0.1, 0.2, 03, 0.4, 0.5, etc., as well as the range values between any two of the above point values.
[0208] In one embodiment, the prepolymer includes a hydroxyl group-containing compound; and / or the cross-linking agent includes an isocyanate group-containing compound.
[0209] The present application does not limit the type of prepolymer, which may include, for example, a hydroxyl-containing compound. The present application does not limit the type of crosslinking agent, which may include, for example, an isocyanate-based compound.
[0210] In one embodiment, the hydroxyl-containing compound includes at least one of polyalkyl alcohol, polyether polyol, polyester polyol, alicyclic alcohol, aromatic alcohol, and polytetramethylene glycol, preferably includes at least one of polyalkyl alcohol, polyether polyol, and polyester polyol; and / or, the isocyanate compound includes at least one of diphenylmethane diisocyanate, 2,4-toluene diisocyanate, and toluene diisocyanate dimer; and / or, the catalyst includes at least one of bismorpholinyl diethyl ether, dimethylcyclohexylamine, and N-methyldicyclohexylamine.
[0211] The hydroxyl-containing compounds of the present application include but are not limited to at least one of polyalkyl alcohols, polyether polyols, polyester polyols, alicyclic alcohols, aromatic alcohols, and polytetramethylene glycol, wherein the hydroxyl group provides a reactive unit that can react with an isocyanate group.
[0212] Preferably, at least one of polyalkyl alcohol, polyether polyol and polyester polyol is included. Polyalkyl alcohol has good flexibility and is a flexible segment in the polyurethane main chain, thereby improving the flexibility of the thermal conductive adhesive. The ether group and the ester group provide the polyurethane with flexibility and low temperature rheological resistance, so that it will not harden at low temperatures and lose its adhesive force.
[0213] The isocyanate-based compound of the present application includes, but is not limited to, at least one of diphenylmethane diisocyanate, 2,4-toluene diisocyanate, and toluene diisocyanate dimer.
[0214] The catalyst of the present application includes but is not limited to at least one of bismorpholinyl diethyl ether, dimethylcyclohexylamine, and N-methyldicyclohexylamine.
[0215] In one embodiment, the tackifier includes at least one of acrylic resin, polyisobutylene, poly-n-butyl vinyl ether, methyl styrene and isobutylene copolymer, and ethylene propylene copolymer, preferably, includes acrylic resin, and the acrylic resin includes at least one of AC1920, AC1010, AC1021, AC1630, AC1632, AC1750, AC2740, and AC3820; and / or, the inorganic filler includes a flame retardant, and the flame retardant includes at least one of magnesium hydroxide, aluminum hydroxide, and borate, and preferably, the surface of the flame retardant is modified with a hydrophobic substance; and / or, the inorganic filler includes a pigment, and the pigment includes magnesium oxide, zinc oxide, aluminum oxide, boron carbide, aluminum nitride, carbon At least one of black, graphite and carbon nanotubes, preferably, the surface of the pigment is modified with a hydrophobic substance; and / or the antioxidant includes at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 168, antioxidant Ultranox626, and antioxidant PEPQ; and / or the anti-ultraviolet absorber includes at least one of 2-(2'-hydroxyphenyl 3',5'-dipentylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, and 2-hydroxy-4-n-octyloxybenzophenone; and / or the coupling agent includes at least one of coupling agent 540, coupling agent 550, coupling agent 560, coupling agent 570, coupling agent 1189, and coupling agent 792.
[0216] The tackifier of the present application includes but is not limited to at least one of acrylic resin, polyisobutylene, poly-n-butyl vinyl ether, methyl styrene and isobutylene copolymer, and ethylene propylene copolymer. Preferably, it includes acrylic resin. The bonding strength of the thermal conductive adhesive mainly depends on the cohesive force of the thermal conductive adhesive and the physical bonding strength provided by the acrylic resin. After the thermal conductive adhesive is used, its bonding strength increases, which mainly depends on the cross-linking and curing of NCO in the adhesive with moisture. After a period of curing, it is completely cured. Acrylic resin includes but is not limited to at least one of AC1920, AC1010, AC1021, AC1630, AC1632, AC1750, AC2740, and AC3820.
[0217] The flame retardant in the present application includes but is not limited to at least one of magnesium hydroxide, aluminum hydroxide, and borate. Preferably, the surface of the flame retardant is modified with a hydrophobic substance. By modifying the surface of the flame retardant with a hydrophobic substance, the dispersibility of the flame retardant in the reaction system can be improved. It can be understood that before the inorganic flame retardant is hydrophobically modified, it is easy to agglomerate, and the agglomeration will cause the thermal conductive adhesive to have particles. The present application uses a hydrophobic substance to modify the surface of the inorganic flame retardant to improve its dispersibility and reduce agglomeration, thereby reducing the phenomenon of particles in the thermal conductive adhesive. After the surface of the inorganic flame retardant is hydrophobically modified, the surface may have organic functional groups, so that the flame retardant can be cross-linked to the organic skeleton of the thermal conductive adhesive, thereby improving the dispersibility and compatibility of the inorganic flame retardant in the thermal conductive adhesive. 。 Furthermore, the flame retardant modifies the hydrophobic substance, making it difficult for the flame retardant to absorb water, improving the flame retardant to bring moisture into the reaction system, thereby reducing the premature curing of the thermal conductive adhesive by moisture, improving the problem of shortening the storage period of the thermal conductive adhesive, and improving the thixotropy of the thermal conductive adhesive, facilitating the stirring and coating of the thermal conductive adhesive.
[0218] The pigments in the present application include but are not limited to at least one of magnesium oxide, zinc oxide, aluminum oxide, boron carbide, aluminum nitride, carbon black, graphite and carbon nanotubes. Preferably, the surface of the pigment is modified with a hydrophobic substance. By modifying the surface of the pigment with a hydrophobic substance, the dispersibility of the pigment in the reaction system can be improved, the agglomeration of the pigment can be reduced, and the phenomenon of particles appearing in the thermal conductive adhesive can be reduced.
[0219] In addition, materials such as magnesium oxide, carbon black, graphite and carbon nanotubes in the pigment are also thermally conductive.
[0220] It is understood that the surface-modified hydrophobic substance in the present application can be a surfactant or a silane coupling agent, and there is no specific limitation. For example, in one embodiment, the specific treatment agent can include an aqueous solution of a silane coupling agent or an alcohol solution of a stearate, and the aqueous solution of a silane coupling agent or the alcohol solution of a stearate is sprayed onto the surface of the material at a high temperature, stirred, and vacuum-activated for modification. For example, in the modification process, the amount of the silane coupling agent is selected to be 0.5% to 1.5% of the mass of the pigment or the mass of the inorganic flame retardant compound, and an addition amount of 1% is more suitable for most applications.
[0221] The antioxidant in the present application includes but is not limited to at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 168, antioxidant Ultranox 626, and antioxidant PEPQ.
[0222] The anti-ultraviolet absorber in the present application includes but is not limited to at least one of 2-(2'-hydroxyphenyl 3',5'-dipentylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, and 2-hydroxy-4-n-octyloxybenzophenone.
[0223] The coupling agent in the present application includes but is not limited to at least one of coupling agent 540 , coupling agent 550 , coupling agent 560 , coupling agent 570 , coupling agent 1189 , and coupling agent 792 .
[0224] In one embodiment, the hydroxyl-containing compound comprises polyalkyl alcohol, polyether polyol, polyester polyol, the polyalkyl alcohol comprises 20 to 40 parts, preferably, 25 to 35 parts, the polyether polyol comprises 20 to 40 parts, preferably, 25 to 35 parts, the polyester polyol comprises 1 to 10 parts, preferably, 3 to 6 parts; and / or, the hydroxyl-containing compound comprises polyalkyl alcohol, the polyalkyl alcohol comprises at least one of polypropylene glycol and polyethylene glycol, preferably comprises polypropylene glycol, the molecular weight of the polypropylene glycol comprises 800 to 4000; and / or, the hydroxyl-containing compound comprises polyether polyol The polyether polyol comprises at least one of polytetramethylene ether glycol, polyether polyol initiated by sucrose and glycerol, toluene diamine polyether polyol and sorbitol polyether polyol, preferably comprises polytetramethylene ether glycol, and the molecular weight range of the polytetramethylene ether glycol comprises 1000 to 8000, preferably 1000 to 3000; and / or the hydroxyl-containing compound comprises polyester polyol, and the polyester polyol comprises crystalline polyester polyol, and the crystalline polyester polyol comprises at least one of polyester DC7380, polyester DC7360, polyester DC7320 and polyester DC7130.
[0225] The hydroxyl-containing compounds of the present application include polyalkyl alcohols, polyether polyols, and polyester polyols. The polyalkyl alcohols include 20 to 40 parts, preferably 25 to 35 parts, the polyether polyols include 20 to 40 parts, preferably 25 to 35 parts, and the polyester polyols include 1 to 10 parts, preferably 3 to 6 parts. The above-mentioned hydroxyl-containing compounds within the above-mentioned range can improve the flexibility and low-temperature rheological resistance of the polyurethane.
[0226] The hydroxyl-containing compound includes polyalkyl alcohol, which includes but is not limited to at least one of polypropylene glycol and polyethylene glycol. Preferably, it includes polypropylene glycol, and the molecular weight of polypropylene glycol is 800 to 4000; polypropylene glycol can improve the fluidity of the thermal conductive adhesive, and the molecular weight has fluidity within a suitable range, thereby improving the processing performance of the thermal conductive adhesive.
[0227] The hydroxyl-containing compound includes, but is not limited to, polyether polyols, which include at least one of polytetramethylene ether glycol, polyether polyols initiated by sucrose and glycerol, toluene diamine polyether polyols, and sorbitol polyether polyols, preferably, polytetramethylene ether glycol, and the molecular weight range of polytetramethylene ether glycol includes 1000 to 8000, preferably, 1000 to 3000. , Polytetramethylene ether glycol can improve the flexibility of thermal conductive adhesive.
[0228] The hydroxyl-containing compound includes polyester polyols, and the polyester polyols include crystalline polyester polyols, and the crystalline polyester polyols include at least one of polyester DC7380, polyester DC7360, polyester DC7320, and polyester DC7130. Crystalline polyester polyols can improve the high and low temperature resistance of the thermal conductive adhesive. It can be understood that the crystalline polyester polyols will melt into a liquid state during the temperature increase process, absorbing heat at this time, and the crystalline polyester polyols will release heat during the temperature reduction process, and the molecular chains will be rearranged to form crystals, that is, when the polyurethane material receives external temperature changes, the crystalline polyester polyols can absorb or release heat (when the temperature of the polyurethane increases, the crystalline polyester polyols absorb heat, and when the temperature of the polyurethane decreases, the crystalline polyester polyols release heat), so that the polyurethane has the characteristics of high and low temperature resistance.
[0229] It is understandable that the hydroxyl-containing compound can include at least two of polyester DC7380, polyester DC7360, polyester DC7320, and polyester DC7130 at the same time, and both polyester with high glass transition temperature and polyester with low glass transition temperature are selected to improve the high temperature and low temperature resistance of the thermal conductive adhesive material. Due to different molecular structures and segment structures, the high temperature and low temperature resistance range caused by the difference in glass transition temperature will be widened, and the high glass transition temperature has high temperature resistance, and the low glass transition temperature has low temperature resistance.
[0230] In one embodiment, the present application also provides a battery, the battery comprising the thermal conductive adhesive as described above.
[0231] For example, thermal conductive adhesive is provided between the battery cells in the battery module and the inner surface of the module, and thermal conductive adhesive is provided between the battery cells and the water cooling plate.
[0232] Since the thermal conductive adhesive adopts all the technical solutions of all the above embodiments, it at least has all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0233] It is understandable that batteries include secondary batteries, battery modules, and battery packs.
[0234] In one embodiment, the present application further provides an electrical device, which includes the above-mentioned battery.
[0235] Since the battery adopts all the technical solutions of all the above embodiments, it has at least all the beneficial effects brought by the technical solutions of the above embodiments, which will not be described one by one here.
[0236] Example
[0237] Example 1
[0238] Prepare ingredients: 100 servings in total.
[0239] The hydroxyl-containing compound (prepolymer) includes: polyalkylene glycol PPG2000 (35.4 parts), polyether polyol PTMEG2000 (12.5 parts), polyester polyol: polyester DC7360 (20.8 parts), polyester DC7320 (5.2 parts); crosslinking agent: MDI-100 (diphenylmethane diisocyanate) (11.4 parts); catalyst: bismorpholinyl diethyl ether (0.31 parts); tackifier: acrylic resin AC1920 (6.5 parts); pigment (inorganic filler): aluminum oxide (1.0 parts); flame retardant (inorganic filler): magnesium hydroxide (6.5 parts); antioxidant: antioxidant 168 (0.21 parts); anti-ultraviolet absorber: 2-(2'-hydroxyphenyl 3',5'-dipentylphenyl) benzotriazole (0.16 parts).
[0240] The steps of production in a 100L reactor are as follows:
[0241] Preheat the molten material: polyester polyol DC7360 is baked at 120℃ 48 hours in advance until it melts into a fluid state, polyester polyol DC7320 is baked at 120℃ 48 hours in advance. MDI-100 is baked at 80℃ for 12 hours until it is completely clear liquid.
[0242] Weighing materials: Weigh liquid polyalkylene glycol PPG2000, polyether PTMEG2000, polyester 7360, polyester 7320, polyacrylic resin AC1920, carbon black and magnesium hydroxide into a stirring kettle according to weight.
[0243] Dehydration: The raw materials in the above-mentioned stirred tank were heated, stirred, and vacuumed to remove water. The dehydration temperature was 130°C, the vacuum degree was -0.097MPa, the dehydration time was 3h, and the speed of the dispersion disk (the structure is shown in Table 2, the material is 304 stainless steel, the dispersion disk diameter is 800mm, and the diameter of the 100L reactor is 1300mm) was 500rpm. After stirring and removing water, a dehydrated mixture was obtained.
[0244] Polymerization: Add MDI-100 (cross-linking agent) to the dehydrated mixture in the stirring kettle. Under an inert atmosphere, stir with a dispersion disk to obtain a mixed intermediate product. The temperature of the stirring kettle should be 15°C lower than the polymerization temperature (polymerization temperature is 125°C). During the polymerization process, sample and test the viscosity every half hour.
[0245] Add the catalyst, antioxidant and anti-ultraviolet absorber to the above mixed intermediate product, heat and stir with a dispersion plate. The catalyst, antioxidant and anti-ultraviolet absorber are added when the viscosity of the reaction system is polymerized to about 150,000 mPa.s.
[0246] End point of polymerization: When the viscosity of the material is detected to be about 180,000 mPa.s, stop heating. Immediately clean the stirring equipment at 120°C while it is still hot to avoid the temperature dropping, which will make it difficult to clean the stirring equipment.
[0247] Discharging: Push the reactor into the press quickly and press the material. Pressing must be completed within 1 hour after the end of the reaction.
[0248] Wash the tank: Clean the glue on the inner wall of the reactor while it is still hot to ensure that the reactor is clean.
[0249] Example 2
[0250] On the basis of Example 1, inorganic pigments and inorganic flame retardants are subjected to surface hydrophobic modification, and the steps of surface hydrophobic modification are as follows: placing an inorganic raw material (such as alumina) in a high-speed mixer, heating to 90° C., spraying a silane coupling agent (KH560) aqueous solution on the surface of the inorganic raw material, and then mixing at 110° C. for 30 minutes to obtain the modified substance. The amount of the silane coupling agent is selected to be 1% of the mass of the inorganic raw material, and the dilution concentration of the silane coupling agent aqueous solution is 0.4wt.%.
[0251] Example 3
[0252] On the basis of Example 2, during the process of adding the catalyst, the antioxidant and the anti-ultraviolet absorber, a coupling agent was added at the same time to obtain Example 3.
[0253] Table 1 Recipe list
[0254]
[0255] Table 2 Preparation process list
[0256]
[0257] Comparative Example 1
[0258] As shown in Table 2, on the basis of Example 1, the process conditions were changed (using a dispersion disk for stirring at a rotation speed of 200 rpm) to obtain Comparative Example 1.
[0259] Performance Testing
[0260] 1. Viscosity test steps: The constant temperature bath is maintained at 25±0.5℃, and the viscosity is tested using a ROTAVISCME-V1 rotational viscometer at a speed of 10r / min. The test is performed three times and the average value is taken.
[0261] 2. Storage stability test: The test method is to seal the prepared samples with packaging cans, place them in an electric blast drying oven, set the temperature to 50°C, and store them for 6 months. After the expiration date, open the sealed cover and observe whether the surface layer of the glue is crusted.
[0262] 3. Elongation at break test steps: Test in accordance with the provisions of GB / T528-2009, using type II dumbbell. Sample preparation: After heating the original packaging tube at 120℃ for 1.5h, use a glue gun to squeeze out the injection film directly from the packaging tube to fill the mold frame, do not bring in bubbles, and scrape it flat with a knife. The bottom of the mold frame should be flat and smooth, and no warping. The surface should be clean and free of oil and impurities. The coating requires one-time molding, and the film should be formed evenly during molding, so that the film thickness is 2±0.2mm. After being placed under standard test conditions for 7 days, the cutting test is carried out, and each group of tests is not less than 5 pieces. The tensile rate is 500mm / min±50mm / min.
[0263] 4. Tensile shear strength test steps: Substrate requirements: PP sheet (100mmⅹ25mmⅹ2.5mm), PC sheet (100mmⅹ25mmⅹ2.5mm), PP substrate needs to be plasma treated. Test piece preparation: Use ethanol to remove dust and oil on the surface of PP and PC test pieces, and use a plasma flame machine to treat the PP surface. After heating the original packaging tube at 120℃ for 1.5h, prepare the sample according to the method specified in GB / T 7124-2008. The overlapping adhesive layer is required to be evenly formed at one time, with a length of 25±2mm and a thickness of 1±0.2mm. The excess adhesive squeezed out is scraped off with a scraper. Each group consists of 5 test pieces. The prepared test pieces are placed under standard conditions for 14 days.
[0264] Constant temperature and humidity aging tensile shear strength test steps: Take a group of test pieces, place them at 85±2℃, 85±2RH% for 14 days, then place them under standard conditions for 24h, and perform tensile test at a tensile rate of 9.0mm / min.
[0265] 5. Thermal conductivity test:
[0266] Thermal conductivity is tested using the transient plane heat source method (Hot Disk) ISO22007-2. A temperature probe with a self-heating function is placed under a sample with a diameter greater than 30mm and a thickness greater than 2mm. The sample disc is pressed with a weight in a balance. During the test, a constant heating power is applied to the probe to increase its temperature. The relationship between the thermal resistivity of nickel - temperature and resistance is linear, and the heat loss can be obtained by testing the change in resistance, thereby measuring the thermal conductivity of the sample.
[0267] 6.Tensile strength test of aluminum interface:
[0268] (1) Dimensions: The dimensions and manufacturing of tensile specimens shall refer to GB / T 6329. A fixture shall be used to accurately position the adhesive joints. Unless otherwise specified, the thickness of the adhesive layer is generally designed to be 0.25±0.05mm / 1.0±0.05mm. It can be controlled by inserting spacer wires parallel to the direction of force application.
[0269] (2) Substrate: The test piece is made of 3003Al substrate. The surface of the bonding object should be cleaned with alcohol before bonding to ensure that there is no contaminants such as grease.
[0270] (3) Preparation process: Complete the bonding sample within the specified operation time, and pay attention to removing the excess glue. After the bonding sample is cured according to the specified conditions, it is tested under the specified conditions.
[0271] (4) Test requirements: The tensile testing machine is tested at a constant test speed of 5 mm / min. If the pull-off displacement needs to be tested, an extensometer is required for measurement.
[0272] Table 3 Performance parameter list
[0273]
[0274] As can be seen from Table 3 above, by comparing Example 1 and Comparative Example 1, the use of a dispersion plate for rapid stirring during the stirring process can improve the phenomenon of particles appearing in the thermally conductive adhesive, thereby improving the shear resistance of the bonding. And by comparing the examples and the comparative examples, the comprehensive performance of the thermally conductive adhesive is improved by using the formula of the present application. Applying the thermally conductive adhesive of the present application as a heat-conducting medium between the heat dissipation surface of the battery and the cooling system can improve the heat dissipation of the power battery as soon as possible when a large amount of heat is generated during the charging and discharging process, and transfer the heat to the inside of the battery in a low temperature environment.
[0275] Table 4 Effect of stirring method
[0276]
[0277]
[0278] On the basis of Example 1, the dispersion method was changed to obtain Examples 4 to 6 and Comparative Examples 2 to 5.
[0279] It can be seen from Table 4 that when the stirring method is independently a stirring paddle, particles appear in the thermal conductive adhesive. When the stirring method includes a dispersion disk and the speed of the dispersion disk is greater than or equal to 300 rpm, particles are not likely to appear in the thermal conductive adhesive.
[0280] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention's specification and drawings, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a thermally conductive adhesive, characterized in that: include: Preparing a formulation component of a thermally conductive adhesive, wherein the formulation component of the thermally conductive adhesive includes a prepolymer, a cross-linking agent, a catalyst, and an inorganic filler; The formula components are heated and stirred to obtain a thermal conductive adhesive, wherein the stirring method includes stirring with a dispersion disk, and the stirring speed ranges from 300 rpm to 2000 rpm.
2. The method for preparing the thermally conductive adhesive according to claim 1, characterized in that: During the process of heating and stirring the formulation components, the stirring speed ranges from 600 rpm to 1000 rpm.
3. The method for preparing the thermally conductive adhesive according to claim 1 or 2, characterized in that: The step of heating and stirring the formula components to obtain the thermal conductive adhesive comprises: The prepolymer and the inorganic filler are mixed and stirred and dehydrated by a dispersion disk to obtain a dehydrated mixture; Mixing the cross-linking agent with the dehydrated mixture, heating and stirring under an inert atmosphere to obtain a mixed intermediate product; The catalyst is added into the mixed intermediate product, and the mixture is heated and stirred to obtain a thermal conductive adhesive.
4. The method for preparing the thermally conductive adhesive according to claim 3, characterized in that: In the step of mixing the crosslinking agent with the dehydrated mixture, heating and stirring under an inert atmosphere to obtain a mixed intermediate product, the stirring method includes stirring with a dispersion disk; And / or, in the step of adding the catalyst to the mixed intermediate product, heating and stirring to obtain the thermally conductive adhesive, the stirring method includes stirring with a dispersion disk.
5. The method for preparing the thermally conductive adhesive according to claim 3 or 4, characterized in that: In the step of mixing the prepolymer and the inorganic filler and stirring and removing water through a dispersion disk to obtain a dehydrated mixture, the step further includes: The prepolymer and the inorganic filler are mixed and stirred by a dispersion plate, heated, and vacuumed to remove water.
6. The method for preparing the thermally conductive adhesive according to claim 5, characterized in that: The heating temperature range is 120°C to 140°C; And / or, the vacuum degree of the vacuum pumping ranges from -0.095 MPa to -0.1 MPa; And / or, during the vacuum dehydration process, the dehydration time ranges from 2h to 5h; And / or, after the vacuum removal of water, the total water content of the prepolymer and the inorganic filler is less than 0.1%.
7. The method for preparing the thermally conductive adhesive according to any one of claims 3 to 6, characterized in that: Before the step of mixing the prepolymer and the inorganic filler and stirring and removing water through a dispersion disk to obtain a dehydrated mixture, the method further comprises: The prepolymer is preheated and melted; and / or the cross-linking agent is preheated and melted.
8. The method for preparing the thermally conductive adhesive according to any one of claims 3 to 6, characterized in that: The formula components of the thermal conductive adhesive also include a tackifier, and in the step of mixing the prepolymer and the inorganic filler and stirring and removing water through a dispersion disk to obtain a dehydrated mixture, the following steps are also included: The prepolymer, the inorganic filler and the thickener are mixed, stirred and dehydrated by a dispersion disk to obtain a dehydrated mixture.
9. The method for preparing the thermally conductive adhesive according to any one of claims 3 to 8, characterized in that: Before the step of mixing the cross-linking agent with the dehydrated mixture, heating and stirring under an inert atmosphere to obtain a mixed intermediate product, the method further comprises: The temperature of the dehydrated mixture is controlled to be 15°C to 30°C lower than the polymerization temperature, and the polymerization temperature is 120°C to 130°C.
10. The method for preparing the thermally conductive adhesive according to any one of claims 3 to 9, characterized in that: The formula components of the thermal conductive adhesive also include at least one of an antioxidant, an anti-ultraviolet absorber, and a coupling agent; The step of adding the catalyst to the mixed intermediate product, heating and stirring to obtain the thermal conductive adhesive also includes: The catalyst and at least one of the antioxidant, the anti-ultraviolet absorber and the coupling agent are added to the mixed intermediate product, heated, vacuumized and stirred to obtain a thermal conductive adhesive.
11. The method for preparing the thermally conductive adhesive according to claim 10, characterized in that: Before the step of adding the catalyst to the mixed intermediate product and heating and stirring to obtain the thermal conductive adhesive, the method comprises: The viscosity of the mixed intermediate product is tested. When the viscosity of the mixed intermediate product is in a range of 100,000 mPa.s to 170,000 mPa.s, the catalyst is added to the mixed intermediate product.
12. The method for preparing the thermally conductive adhesive according to any one of claims 3 to 11, characterized in that: After the cross-linking agent is mixed with the dehydrated mixture, heated and stirred under an inert atmosphere to obtain a mixed intermediate product, the method further comprises: The viscosity of the mixed intermediate product is tested at every preset time, preferably, the preset time includes 0.5h to 1h.
13. The method for preparing the thermally conductive adhesive according to any one of claims 9 to 12, characterized in that: The step of adding the catalyst to the mixed intermediate product, heating and stirring to obtain the thermal conductive adhesive comprises: The catalyst is added to the mixed intermediate product, heated and stirred to obtain a mixed product, and the viscosity of the mixed product is tested. When the viscosity of the mixed product is in the range of 180,000 mPa.s to 200,000 mPa.s, heating is stopped to obtain a thermal conductive adhesive.
14. The method for preparing the thermally conductive adhesive according to claim 13, characterized in that: After adding the catalyst to the mixed intermediate product, heating and stirring to obtain a mixed product, and testing the viscosity of the mixed product, when the viscosity of the mixed product is in the range of 180,000 mPa.s to 200,000 mPa.s, stopping heating to obtain the thermal conductive adhesive, the method further includes: Within 1 hour after stopping heating, the thermal conductive adhesive package is discharged.
15. The method for preparing the thermally conductive adhesive according to any one of claims 1 to 14, characterized in that: The prepolymer comprises 41 to 90 parts, preferably 65 to 75 parts; And / or, the cross-linking agent comprises 7 to 15 parts, preferably, 9 to 13 parts; in 0.4 parts; And / or, the inorganic filler includes a flame retardant, 5 to 10 parts, preferably, 8 to 10 parts; And / or, the inorganic filler includes pigment, 1 to 3 parts, preferably greater than 1 part and less than or equal to 2 parts; And / or, the formula components of the thermal conductive adhesive further include 5 to 10 parts of a tackifier, preferably 6 to 8 parts; And / or, the formula components of the thermal conductive adhesive further include an antioxidant, 0.1 to 0.5 parts, preferably 0.2 to 0.4 parts; And / or, the formula components of the thermal conductive adhesive further include an anti-ultraviolet absorber, 0.1 to 0.5 parts, preferably 0.2 to 0.4 parts; And / or, the formula components of the thermal conductive adhesive also include a coupling agent, 0.5 to 1 part, preferably, 0.7 to 0.9 part.
16. The method for preparing the thermally conductive adhesive according to any one of claims 1 to 15, characterized in that: The prepolymer includes a hydroxyl-containing compound; And / or, the cross-linking agent includes an isocyanate-based compound.
17. The method for preparing the thermally conductive adhesive according to claim 16, characterized in that: The hydroxyl-containing compound comprises at least one of polyalkyl alcohol, polyether polyol, polyester polyol, alicyclic alcohol, aromatic alcohol, polytetrahydrofuran polyol, preferably at least one of polyalkyl alcohol, polyether polyol, polyester polyol; And / or, the isocyanate compound includes at least one of diphenylmethane diisocyanate, 2,4-toluene diisocyanate, and toluene diisocyanate dimer; And / or, the catalyst includes at least one of bismorpholinyl diethyl ether, dimethylcyclohexylamine, and N-methyldicyclohexylamine.
18. The method for preparing the thermally conductive adhesive according to any one of claims 15 to 17, characterized in that: The formula components of the thermal conductive adhesive also include a tackifier, and the tackifier includes at least one of acrylic resin, polyisobutylene, poly-n-butyl vinyl ether, methyl styrene and isobutylene copolymer, and ethylene propylene copolymer. Preferably, the tackifier includes acrylic resin, and the acrylic resin includes at least one of AC1920, AC1010, AC1021, AC1630, AC1632, AC1750, AC2740, and AC3820; And / or, the inorganic filler includes a flame retardant, and the flame retardant includes at least one of magnesium hydroxide, aluminum hydroxide, and borate, and preferably, the surface of the flame retardant is modified with a hydrophobic substance; and / or, the inorganic filler comprises a pigment, the pigment comprises at least one of magnesium oxide, zinc oxide, aluminum oxide, boron carbide, aluminum nitride, carbon black, graphite and carbon nanotubes, preferably, the surface of the pigment is modified with a hydrophobic substance; And / or, the formula components of the thermal conductive adhesive further include an antioxidant, and the antioxidant includes at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 168, antioxidant Ultranox 626, and antioxidant PEPQ; And / or, the formula components of the thermal conductive adhesive further include an anti-ultraviolet absorber, and the anti-ultraviolet absorber includes at least one of 2-(2'-hydroxyphenyl 3',5'-dipentylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-octylphenyl)benzotriazole, and 2-hydroxy-4-n-octyloxybenzophenone; And / or, the formula components of the thermal conductive adhesive further include a coupling agent, and the coupling agent includes at least one of coupling agent 540, coupling agent 550, coupling agent 560, coupling agent 570, coupling agent 1189, and coupling agent 792.
19. The method for preparing the thermally conductive adhesive according to claim 16 or 17, characterized in that: The hydroxyl-containing compound includes polyalkyl alcohol, polyether polyol, polyester polyol, the polyalkyl alcohol includes 20 to 40 parts, preferably, 25 to 35 parts, the polyether polyol includes 20 to 40 parts, preferably, 25 to 35 parts, and the polyester polyol includes 1 to 10 parts, preferably, 3 to 6 parts; And / or, the hydroxyl-containing compound comprises a polyalkyl alcohol, the polyalkyl alcohol comprises at least one of polypropylene glycol and polyethylene glycol, preferably comprises polypropylene glycol, and the molecular weight of the polypropylene glycol comprises 800 to 4000; And / or, the hydroxyl-containing compound comprises a polyether polyol, the polyether polyol comprises at least one of polytetramethylene ether glycol, a polyether polyol initiated by sucrose and glycerol, a toluene diamine polyether polyol, and a sorbitol polyether polyol, preferably comprises polytetramethylene ether glycol, and the molecular weight range of the polytetramethylene ether glycol comprises 1000 to 8000, preferably, 1000 to 3000; And / or, the hydroxyl-containing compound includes polyester polyol, the polyester polyol includes crystalline polyester polyol, and the crystalline polyester polyol includes at least one of polyester DC7380, polyester DC7360, polyester DC7320, and polyester DC7130.
20. A thermally conductive adhesive, characterized in that: The thermally conductive adhesive comprises the thermally conductive adhesive obtained by the preparation method of the thermally conductive adhesive according to any one of claims 1 to 19.
21. A battery, characterized in that: The battery comprises the thermally conductive adhesive obtained by the preparation method of the thermally conductive adhesive according to any one of claims 1 to 19.
22. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 21.
Citation Information
Patent Citations
Secondary battery and production method thereof
CN105647460A
Heat-conducting adhesive and secondary battery containing heat-conducting adhesive
CN105670550A
Heat-conducting polyurethane pouring sealant for new energy vehicle battery and preparation method of heat-conducting polyurethane pouring sealant
CN111607351A
Preparation method of heat-conducting structural adhesive
CN115678481A
Method and device for synthesizing heat-conductive glue
CN1966597A